Rice black‐streaked dwarf virus P10 acts as either a synergistic or antagonistic determinant during superinfection with related or unrelated virus. (14th February 2019) - Zhang, Hehong; Tan, Xiaoxiang; He, Yuqing; Xie, Kaili; Li, Lulu; Wang, Rong; Hong, Gaojie; Li, Junmin; Li, Jing; Taliansky, Michael; MacFarlane, Stuart; Yan, Fei; et al.
Summary: Rice black‐streaked dwarf virus (RBSDV), a member of the genus Fijivirus, is a devastating pathogen of crop plants. RBSDV S10 encodes a capsid protein (P10) that is an important component of the double‐layered particle. However, little information is available on the roles of RBSDV P10 in viral infection or in interactions with other viruses. Here, we demonstrate that the expression of P10 in plants alleviates the symptoms of both RBSDV and the closely related Southern rice black‐streaked dwarf virus (SRBSDV), and reduces the disease incidence, but renders the plants more susceptible to the unrelated Rice stripe virus (RSV). Further experiments suggest that P10‐mediated resistance to RBSDV and SRBSDV operates at the protein level, rather than the RNA level, and is not a result of post‐transcriptional gene silencing. Transcriptomic data reveal that the expression of P10 in plants significantly suppresses the expression of rice defence‐related genes, which may play important roles in resistance to RSV infection. After infection with RBSDV, plants are more resistant to subsequent challenge by SRBSDV, but more susceptible to RSV. Overall, these results indicate that P10 acts as an important effector in virus interactions.